2013
DOI: 10.1038/cddis.2013.425
|View full text |Cite
|
Sign up to set email alerts
|

Light-controlled inhibition of malignant glioma by opsin gene transfer

Abstract: Glioblastomas are aggressive cancers with low survival rates and poor prognosis because of their highly proliferative and invasive capacity. In the current study, we describe a new optogenetic strategy that selectively inhibits glioma cells through light-controlled membrane depolarization and cell death. Transfer of the engineered opsin ChETA (engineered Channelrhodopsin-2 variant) gene into primary human glioma cells or cell lines, but not normal astrocytes, unexpectedly decreased cell proliferation and incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 44 publications
0
21
0
1
Order By: Relevance
“…; Aprea & Calegari, ; Levin, , ; Pai & Levin, ; Yang et al . ; Wang et al . ), we believe that application of optogenetics to non‐neural, non‐excitable cells will become a transformative tool for understanding the role of biophysical signals in numerous birth defects.…”
Section: Discussionmentioning
confidence: 99%
“…; Aprea & Calegari, ; Levin, , ; Pai & Levin, ; Yang et al . ; Wang et al . ), we believe that application of optogenetics to non‐neural, non‐excitable cells will become a transformative tool for understanding the role of biophysical signals in numerous birth defects.…”
Section: Discussionmentioning
confidence: 99%
“…A wide variety of opsins exist in vertebrates as photoreceptors, and each has an optimal wavelength. The first report of the relationship between opsins and tumor suppression was reported by Yang et al, who showed that opsin gene transfers with blue LED irradiation inhibited the growth of malignant glioma. In the opsin family, Opn3 is known as a blue light receptor and is widely expressed in non‐visual cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to remote control of excitable cells, optogenetic techniques have been used to induce and study cell death. For instance, Yang et al showed that an optogenetic approach can induce apoptotic cell death in human glioma cells via depolarization of cell membrane potential and influx of Ca 2+ (26). In another study, Hill et al reported a two-photon chemical apoptotic targeted ablation technique (27).…”
Section: Introductionmentioning
confidence: 99%